Odpowiedzi

Najlepsza Odpowiedź!
2010-01-30T12:09:41+01:00
A(2ab+b)-b(a-2ab+a^) ^ oznacza potege 2

2a^b+ab-ab+2ab^-a^b=2a^b+2ab^-a^b-- zredukowane

obliczam
2*(0,1)^*(-10)+2*(0,1)*10^-(0,1)^*(-10)= -0,2+20-(0,01*-10)= 19,8+0,1=19,9
2010-01-30T12:17:03+01:00
A(2ab+b)-b(a-2ab+a(do pot. 2)) dla a=0.1 i b= -10
2a + a(do potęgi 2) + ab +ab - ab + 2b - ab + b(do pot. 2) + a(do pot.2)=
=2a + a(do pot. 2) + 2b b(do pot. 2) + a(do pot.2)=
= 2a + 2a(do pot. 2) + 2b + b(do pot.2)=
=2 x 0,1 + 2 x (0,1)(do pot.2) + 2 x (-10) + (-10) (do pot.2)=
0,2 + 0,02 - 20 + 100= 0,22 - 20 + 100= 0,22 + 80= 80,22